Aid Volatility and Dutch Disease : Is There a Role for Macroeconomic Policies? - Tressel, Thierry (IMF Working Papers; Working Paper ;, 2006)
This paper studies how macroeconomic policies can help offset two unintended and undesirable features of foreign aid: its volatility and Dutch disease. We present evidence that aid volatility augments trade balance volatility and that foreign aid, with the important exception of years of adverse shocks, depresses exports. We also find that these effects can be mitigated through changes in net domestic assets of the central bank-a variable that reflects both monetary and fiscal policy. To characterize the optimal policy, we develop a general equilibrium model in which the capital account is closed and aid influences productivity growth through positive (public expenditure) and negative (Dutch disease) externalities. In this setting, macroeconomic policies permanently affect real variables and can improve welfare if donors do not distribute foreign aid optimally over time.